Pengungkapan Corporate Social Responsibility (CSR) Dan Penghindaran Pajak: Kepemilikan Institusional Sebagai Variabel Moderasi - Amalia, Firda Ayu (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
The purpose of this study was to empirically examine the effect of the effect of disclosure of Corporate Social Responsibility (CSR) on tax avoidance by adding institutional ownership as a moderating variable. This research is based on legitimacy theory, which explains that every company always tries to get positive recognition or legitimacy from the community. The sampling technique uses purposive sampling with predetermined criteria. The sample used was 45 manufacturing companies listed on the Indonesian Stock Exchange in the 2017 period. This study uses a moderating regression analysis method, moderated regression analysis (MRA), with SPSS version 24 analysis tool to analyze data and test hypotheses. The results of the study prove that there is a positive relationship to the effect of CSR disclosure on tax avoidance. Furthermore, institutional ownership cannot moderate the relationship of CSR and tax avoidance. Keywords: Tax Avoidance; CSR; Institutional Ownership.